(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The remainder of the pavement system is supported by the subgrade, the soil layer on top of which the subbase or pavement is constructed. The California Bearing Ratio (CBR) value of a subgrade must be at least 10. This is essential for highway engineers. Numerous studies demonstrate that if a subgrade has If the subbase material has a CBR value < 10, it will deflect under traffic loads in a similar way to the subgrade and harm the pavement. Pavement drainage and stability are provided by the subbase, a layer of aggregate material immediately beneath the pavement. The inferior, that Undrained water can freeze and expand in the layers supporting the pavement, placing intense internal strain on the pavement structure. Additionally, running water can transport debris from the subbase or subgrade and, in conjunction with traffic, pump it out of the drains. Highway engineers must consequently provide a solid, permeable subbase with longitudinal sub-drains. The effects of saturation on the stability of the soil subgrade are reviewed in this essay.